2010
DOI: 10.1007/s00586-010-1600-x
|View full text |Cite
|
Sign up to set email alerts
|

Axial pain after posterior cervical spine surgery: a systematic review

Abstract: Posterior operative approach has been the standard treatment for cervical compressive myelopathy, and axial pain after laminoplasty or laminectomy as a postoperative complication is now gradually receiving more and more attention. The objective of this study was to provide a systematic review of the current understanding of axial pain after cervical laminoplasty and laminectomy, and summarize clinical features, influence factors and preventive measures of axial pain after posterior decompressive surgery based … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
99
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 120 publications
(102 citation statements)
references
References 48 publications
3
99
0
Order By: Relevance
“…15,17 In contrast, Asian spine surgeons developed EL and usually prefer it. Strict indications for LF and EL differ according to cervical lordosis and instability.…”
Section: Discussionmentioning
confidence: 99%
“…15,17 In contrast, Asian spine surgeons developed EL and usually prefer it. Strict indications for LF and EL differ according to cervical lordosis and instability.…”
Section: Discussionmentioning
confidence: 99%
“…Cervical spine decompression surgery has been frequently performed to gain neurologic recovery and pain reduction to improve functional outcome . However, persistent pain following cervical spine surgery is not uncommon .…”
Section: Introductionmentioning
confidence: 99%
“…1 The advantages of the posterior approach compared with the anterior approach include indirect decompression without destabilizing the disk space, intuitive operation while exposing multiple levels, and less risk of postoperative instability and adjacent level degeneration. [2][3][4] Studies have reported more satisfactory surgical outcomes using laminoplasty or laminectomy [5][6][7][8] ; however, postoperative problems, such as C5 palsy, axial pain, segmental instability, restriction of neck motion, perineural adhesions, and loss of lordotic curvature, have also been reported.…”
Section: Introductionmentioning
confidence: 99%